(untitled) (EAAE Annual Conference Proceedings, 2020)
Architecture is an eminently artificial human enterprise but subject to natural laws and principles residing somewhere between the mineral world and vegetation. It is eminently archaic, as the dominant epistemologies, pragmatic conditions and techniques may change, but fundamental notions, ideas and principles remain where they have been ever since the construction of the first shelter. Architecture is also eminently thingly. As a thing, every work of architecture is in opposition to our broken world of events. For better or for worse, in actual practice this opposition settles in the act of construction, as a project becomes a building: material, structure, space.